2017
DOI: 10.1017/thg.2017.15
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Family Cohesion Moderates Environmental Influences on Prosocial Behavior in Nigerian Adolescent Twins

Abstract: Research shows that perceived family cohesion is positively related to prosocial behavior in adolescents. In this study, we investigated heritability of prosocial behavior (PB) and perceived family cohesion (FC) among Nigerian twins attending public schools in Lagos State, Nigeria (mean age = 14.7 years, SD = 1.7 years), and explored the issue of whether children's perception of cohesive family environment moderated genetic and environmental influences on (PB). The PB scale of the Strengths and Difficulties Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 42 publications
2
18
0
1
Order By: Relevance
“…There is consistent evidence supporting the role of genetics in individual differences in prosocial behavior (e.g., Gregory, Light-Häusermann, Rijsdijk, & Eley, 2009;Hur, Taylor, Jeong, Park, & Haberstick, 2017; see Knafo-Noam, Vertsberger, & Israel, 2018, for review). This has been supported with parent-reported and labbased prosocial behavior in subsamples of the current twins (Knafo et al, 2011;Knafo-Noam, Uzefovsky, Israel, Davidov, & Zahn-Waxler, 2015).…”
Section: Discussionmentioning
confidence: 94%
“…There is consistent evidence supporting the role of genetics in individual differences in prosocial behavior (e.g., Gregory, Light-Häusermann, Rijsdijk, & Eley, 2009;Hur, Taylor, Jeong, Park, & Haberstick, 2017; see Knafo-Noam, Vertsberger, & Israel, 2018, for review). This has been supported with parent-reported and labbased prosocial behavior in subsamples of the current twins (Knafo et al, 2011;Knafo-Noam, Uzefovsky, Israel, Davidov, & Zahn-Waxler, 2015).…”
Section: Discussionmentioning
confidence: 94%
“…The difference between monozygotic and dizygotic correlations for PB was larger in females than in males, suggesting that genetic effects on PB may be larger in females than in males. However, model-fitting analysis indicated that the magnitudes of genetic and environmental effects were not significantly different between the two sexes (Hur et al, 2017). Polychoric correlations for FRA were 0.78 (95% CI = 0.63, 0.88) for MZM, 0.64 (95% CI = 0.51, 0.74) for DZM, 0.75 (95% CI = 0.64, 0.84) for MZF, 0.76 (95% CI = 0.67, 0.83) for DZF and 0.76 (95% CI = 0.68, 0.82) for OSDZ twins.…”
Section: Descriptive Statistics and Twin Correlationsmentioning
confidence: 89%
“…We also hope that the NTSR can be expanded to include children and adolescents in private schools in Nigeria in the near future to better assess the effects of socioeconomic status on human psychological development. Hur, Taylor et al, (2017) Moderation effects of family cohesion on prosocial behavior FC significantly moderated E unique to PB (E × E interaction). A for PB was stable across all levels of FC.…”
Section: Future Directionsmentioning
confidence: 97%
“…E for PB was highest when FC was lowest and decreased as the levels of FC increased, suggesting that FC reduces individual differences in PB by changing environmental experiences rather than genetic factors in PB. Hur, Taylor et al, (2017) Moderation effects of religious attendance on prosocial behavior…”
Section: Future Directionsmentioning
confidence: 99%